Study of eosinophil cationic protein serum levels in patients with toxocariasis - Eleonara Marinova Kaneva (Emergency Department of Hospital San Pedro (Logroño, Spain), 2020)
Introduction: Toxocariasis is a zoonotic helminth infection with difficult diagnosis. Determination of specific IgG antibodies alone does not allow to establish the disease stage and to evaluate the treatment efficacy. Therefore it is necessary to identify additional markers that will assist the diagnosis. The purpose of our study was to identify and monitor eosinophil cationic protein (ECP) levels in patients with toxocariasis confirmed by serology and to compare our data with the literature to determine the relevance of this protein as an indicator for recent infection and the effectiveness of the therapy. Material and methods: ELISA (CUSABIO) commercial kit was used for determination of ECP concentration. Sixty serum samples were studied from individuals previously tested and confirmed for toxocariasis by the presence of specific anti-Toxocara IgG antibodies in ELISA (Toxocara IgG Rbiopharm) and the presence of specific bands in Western blot as confirmatory test (LD BIO). Twenty serum samples from clinically healthy blood donors were used as a control group. Results: The mean concentration of serum ECP in the patients with toxocariasis was significantly higher than in clinically healthy subjects. Seventy-two percent of patients affected by toxicariasis showed increased serum concentration of ECP. However, no statistically significant differences were observed in terms of age (p = 0.451) and sex (p = 0.682) of the patients or clinical form of the disease. ECP levels among patients with visceral toxocariasis were relatively higher (mean 22.99 ng / ml ± 13.16 SD) in comparison to those with ocular involvement (15.60 ng/ml ± 9.92 SD). Correlation between the presence of peripheral eosinophilia and the concentration of serum ECP was not also established. Conclusion: Data from our study give us reason to believe that serum levels of ECP could serve as an additional marker indicating recent infection, especially in patients without marked increase in the blood eosinophils.